Positive emotions at work: a study on home care workers for older people - Holden-Peters, Jan Jordi (2005)
This thesis takes a rare and exploratory look at the experience of positive emotions in work settings, examining their causes and consequences. It begins by reviewing and offering a critique of previous organisational research related to this topic, which has tended to focus on the rather narrow concept of job satisfaction. In line with a recent theory of workplace affect (Weiss & Cropanzano, 1996), it is argued that a more in-depth look at positive emotions as momentary reactions to events may improve our understanding of how workplace positive affect is linked to various organisational outcomes.